1998
DOI: 10.1111/j.1745-6592.1998.tb00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of MTBE Relative to Benzene in a Gasoline‐Contaminated Aquifer (1993–98)

Abstract: Methyl tert‐butyl ether (MTBE) and benzene have been measured since 1993 in a shallow, sandy aquifer contaminated by a mid‐1980s release of gasoline containing fuel oxygenates. In wells downgradient of the release area, MTBK was detected before benzene, reflecting a chromatographic‐like separation of these compounds in the direction of ground water flow. Higher concentrations of MTBE and benzene were measured in the deeper sampling ports of multilevel sampling wells located near the release area, and also up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 15 publications
2
73
0
1
Order By: Relevance
“…However, this has lead to widespread groundwater contaminations. The relative high water solubility has resulted in frequent occurrences of MTBE and TBA in groundwater and raised public health concerns (Squillace et al 1996;Landmeyer et al 1998;EPA 1999). As a consequence, MTBE is being phased out in the United States.…”
Section: Introductionmentioning
confidence: 98%
“…However, this has lead to widespread groundwater contaminations. The relative high water solubility has resulted in frequent occurrences of MTBE and TBA in groundwater and raised public health concerns (Squillace et al 1996;Landmeyer et al 1998;EPA 1999). As a consequence, MTBE is being phased out in the United States.…”
Section: Introductionmentioning
confidence: 98%
“…For example, the solubility of MTBE from reformulated gasoline (11.1% MTBE by volume) is 4700 mg/L at 20°C, while the solubility of benzene from conventional gasoline is only 18 mg/L (1). Since it only sorbs weakly on solids (Koc ) 11 (2)) and appears difficult to biodegrade (5), it can travel nearly unretarded in groundwater and long plumes of dissolved MTBE are frequently observed (6,7). In several laboratory studies, biodegradation of MTBE by aerobic bacteria has been observed (8)(9)(10)(11), while in others, MTBE was reported to be recalcitrant, in particularly under anaerobic conditions (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Although the potential for aerobic biodegradation of MTBE to nontoxic products has been demonstrated for a number of groundwater (3,9,18) and surface-water sites (5), the actual contribution of this process to natural attenuation of MTBE is unclear because the onset and subsequent predominance of anoxic conditions are characteristics of hydrocarbon-contaminated waters. Consequently, engineered systems are being developed to support aerobic MTBE biodegradation under otherwise anoxic conditions (18).…”
mentioning
confidence: 99%
“…The U.S. Geological Survey national water use summary estimated that 60% of the drinking water consumed in the continental United States comes from surface water (20). Because these systems are not easily shielded from numerous point (5,9) and nonpoint (1, 2, 4, 6, 10, 13, 14, 16) sources of MTBE contamination, identifying natural sinks for MTBE in surface waters is particularly important. Although microorganisms in surfacewater bed sediments can mineralize MTBE to CO 2 under oxic conditions (5), geochemical constraints on oxygen transport (27) may limit the importance of aerobic MTBE mineralization in these systems (5).…”
mentioning
confidence: 99%